The Role of Company Age in Moderating Stock Return of Food and Beverage Companies - Andi Basru Wawo (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
The purpose of this research is to determine the factors that influence the return of shares in food and beverage firms listed on the IDX from 2016 to 2019. Purposive sampling is utilized by as many as 12 companies in the sample selection procedure. Multiple regression analysis and moderation regression analysis were used to analyze the data, with the spss application version 16 for Windows being used. This study revealed that Return on Assets (ROA) had a positive and significant effect on stock returns. In contrast, Net Profit Margin (NPM) and Current Ratio (CR) did not affect stock returns. The age of the company does not affect the effect of Return on Assets (ROA), Net Profit Margin (NPM), and Current Ratio (CR) on stock returns.